Strategi Tutor dalam Memotivasi Belajar Warga Belajar pada Program Paket Kesetaraan Di PKBM Mandiri Bakti - Divana Adelia Candra Pradita; Norhidayat Norhidayat; Mustangin Mustangin; Sri Wahyuni (Universitas Indraprasta PGRI, 2026)
Equivalency education is one of several PKBM programs designed to serve as an alternative to formal education for individuals who have dropped out of school for various specific reasons. The purpose of this study is to determine the learning motivation of students in the equivalency program at PKBM Mandiri Bakti. The focus of the study is on improving teaching methods in Equivalency Programs A, B, and C. An issue identified during observations was that many students lacked interest or motivation to attend the weekly classes. This study is classified as descriptive research utilizing qualitative methods. After the researchers improved the quality of instruction, the tutors at PKBM Mandiri Bakti demonstrated greater proficiency in creative teaching methods. The tutors have incorporated technological advancements and engaging learning processes into their instruction to help maximize student motivation. Students at PKBM Mandiri Bakti exhibit high levels of enthusiasm and have high expectations for the future. This study found evidence that after tutors applied learning strategies, there was an increase in the motivation of students in community learning packages A, B, and C, and their understanding of the subject matter improved significantly. Supporting factors included the adequacy of facilities and infrastructure as well as the tutors’ competence in their respective fields. Meanwhile, the limiting factor was the students’ lack of literacy to explore the material they intended to learn.